2020
DOI: 10.3390/ijms21134815
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Role of HDACs 4 and 5 in the Modulation of Processes Regulating MAFbx and MuRF1 Expression during Muscle Unloading

Abstract: Unloading leads to skeletal muscle atrophy via the upregulation of MuRF-1 and MAFbx E3-ligases expression. Reportedly, histone deacetylases (HDACs) 4 and 5 may regulate the expression of MuRF1 and MAFbx. To examine the HDAC-dependent mechanisms involved in the control of E3-ubiquitin ligases expression at the early stages of muscle unloading we used HDACs 4 and 5 inhibitor LMK-235 and HDAC 4 inhibitor Tasqinimod (Tq). Male Wistar rats were divided into four groups (eight rats per group): nontreated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Meanwhile, HDAC4/GADD45α axis also plays an important role in the prevention of muscle atrophy induced by hind limb unloading in elderly rats (Yoshihara et al, 2019 ). Recent studies have shown that HDAC4 and HDAC5 are involved in muscle atrophy induced by hind limb unloading through the regulation of myogenin (MYOG), ubiquitin, and calpain-1 (Mochalova et al, 2020 ). In conclusion, the role of HDAC4 in skeletal muscle cells is complex, and there are many regulatory molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, HDAC4/GADD45α axis also plays an important role in the prevention of muscle atrophy induced by hind limb unloading in elderly rats (Yoshihara et al, 2019 ). Recent studies have shown that HDAC4 and HDAC5 are involved in muscle atrophy induced by hind limb unloading through the regulation of myogenin (MYOG), ubiquitin, and calpain-1 (Mochalova et al, 2020 ). In conclusion, the role of HDAC4 in skeletal muscle cells is complex, and there are many regulatory molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the improved muscle status with the oil treatment, the increase in atrogenes, MuRF1, and atrogin-1 were not prevented by the oil mixture. It has recently been reported that HDAC-5 inhibition is able to prevent disuse-induced upregulation of atrogin-1 and myogenin, whereas HDAC-4 inhibition was only able to prevent increased myogenin expression [ 55 ]. In addition, it has been proposed that HDAC-4 deacetylates MHC proteins, allowing MuRF-1 to ubiquitinate them, triggering their proteolysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the N2 Bristol (wild-type) strain and RB756 hda-4 (ok518) deletion mutant were used. To synchronize the growth of the worms, an egg preparation was made in a laboratory at the Kennedy Space Center as described previously 28 . All L1 larvae (each strain, 9,000 worms) were kept in a 1-ml plastic syringe in M9 buffer containing 5 mg/L cholesterol (M9C) until the initiation of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 1000 adult worms were collected by thawing the frozen culture samples on ice and washing them three times by natural sedimentation in ice-cold M9 buffer to remove larvae and bacterial food. RNA extraction, microarray analysis, and real-time RT-PCR analysis were performed as described previously 28 , 29 . The following primer pairs were used for PCR amplification: T28A11.19 (forward: 5ʹ-CGA GTG AGT TAG AGA GAA GAA GAA TTA GAA-3ʹ, reverse: 5ʹ-TCT GCT CCA AAT CCA GAA AAA GT-3ʹ), T28A11.2 (forward: 5ʹ-AAA AGA CAA CTG CAT GAA AAA GGA-3ʹ, reverse: 5ʹ-GCC GAC TCC GAT GAA ATG A-3ʹ), C17B7.4 (forward: 5ʹ-CGA ATT GTG CAA AAA CAT GGT T-3ʹ, reverse: 5ʹ-GCG AGT CCT CCT CTC CAC AAG-3ʹ), T20D4.11 (forward: 5ʹ-AGA ACT TGT GGA GGA GCC ATGT-3ʹ, reverse: 5ʹ-AGT CAGC GTC GCA TTG TTT G-3ʹ), T20D4.10 (forward: 5ʹ-CAG TTG CGA CTG GAG CAG AA-3ʹ, reverse: 5ʹ-GGA CAG ACC CAT GAT GCA AGA-3ʹ), C03G6.5 (forward: 5ʹ-GCATGAAGAAGGAGATTACTGAAACA-3ʹ, reverse: 5ʹ-ACC GGA AAG ATT GAC AAA TTG C-3ʹ), and eft-2 (forward: 5ʹ-GAC GCT ATC CAC AGA GGA GG-3ʹ, reverse: 5ʹ-TTC CTG TGA CCT GAG ACT CC-3ʹ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation